The effect of different training modalities on resting hormonal level in active young males - Vajda, Matej; Vanderka, Marián; Buzgó, Gabriel; Sedliak, Milan; Kampmiller, Tomáš (Journal of Applied Biomedicine, 2021)
The purpose of this study was to determine the changes in the resting level of serum cortisol, testosterone and T/C ratio in response to different training modalities and their variations. A secondary purpose was to identify if the various six weeks training programs are an effective way to improve physical fitness. 86 regularly active young males were assigned to one of six groups: Endurance constant running (ECR), Endurance interval running (EIR), Resistance training (RT), Explosive training (ET), Speed-endurance 50 m running (SER50) and Speed-endurance 150 m running (SER150) training. The resting levels of testosterone, cortisol and T/C ratio, as well as physical fitness, were measured. The ECR, EIR, and RT training program decreased COR level (P < 0.05). An increase of the T/C ratio was observed in the ECR and EIR group (P < 0.05). Except for SER50, each training program improved physical fitness. Our results suggest that endurance and resistance training modalities performed with a moderate to vigorous intensity may be a usable way to manage the resting cortisol level and enhance physical fitness in active young males.
Keywords: kondiční příprava; vytrvalostní trénink; hydrokortison; lidé; Humans; Endurance Training; Physical Conditioning, Human; Hydrocortisone